BUSINESS MODEL FOR SPECIAL TRADITIONAL DRINKS OF GRESIK’S IN CURCUMA AND GINGER POTION “ESON” - Rahmi, Vembri Aulia; Ismanto, Hadi; Aslamiyah, Suaibatul; Rosyihuddin, Muhammad (RADJA PUBLIKA, 2026)
The culinary business in Gresik Regency requires attention from at least local stakeholders, not only because of the high consumer interest in its culinary specialties but also because the market for these products is also becoming crowded and saturated. Meanwhile, the potential of this business is actually still vast, supported by the spirit of preserving local wisdom. Another problem that also arises is the level of business competition is also quite high. This study aims to determine how the BMC concept for MSEs practices in Gresik Regency. The focus of this study is to conduct observations on businesses in the culinary sector, specifically traditional beverages, such as sinom and temulawak